2022
DOI: 10.3389/fpsyg.2022.957429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring an EAP writing teacher's adaptive expertise and adaptive teaching practices from a CDST perspective

Abstract: Teachers' adaptive expertise (TAE) has received increasing attention in the current English as foreign language (EFL) teaching field, however, it has seldom been examined with adaptive practices by teachers in on-going classes among existing literature. Adopting a mixed-method design with data triangulation, this study was conducted to explore the complexity of teachers' adaptive expertise (TAE) and adaptive teaching practices that an EAP writing teacher demonstrated in academic writing courses, from a Complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…That is to say, routine and adaptive expertise has similar, but not the same, basic components, and they differ in their knowledge representation with the organization and abstraction of knowledge (Bohle Carbonell et al, 2014). Adaptive experts can flexibly use different types of knowledge, as well as cognitive, metacognitive, social and emotional strategies in their daily practices (Xiang et al, 2022).…”
Section: Teachers' Adaptive and Routine Expertise With Playfulness An...mentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, routine and adaptive expertise has similar, but not the same, basic components, and they differ in their knowledge representation with the organization and abstraction of knowledge (Bohle Carbonell et al, 2014). Adaptive experts can flexibly use different types of knowledge, as well as cognitive, metacognitive, social and emotional strategies in their daily practices (Xiang et al, 2022).…”
Section: Teachers' Adaptive and Routine Expertise With Playfulness An...mentioning
confidence: 99%
“…As the social interactions that occur in daily life at ECE centres are complex, uncertain and ambiguous, teachers' adaptive expertise is characterized by non-linearity, interconnectedness and selforganization (Xiang et al, 2022). Adaptiveness can also be seen as an individual's ability to adjust one's reactions in response to environmental changes (Bohle Carbonell et al, 2014) and to use adequate strategies, including playfulness, to solve problems and relieve tensions (Siklander and Impiö, 2019).…”
Section: Teachers' Adaptive and Routine Expertise With Playfulness An...mentioning
confidence: 99%
“…Based on their literature review results, Bohle Carbonell and colleagues (2014) suggested that both adaptive and routine expertise share the same extent of domain knowledge and skills but differ in their knowledge organization and abstraction. Adaptive experts can flexibly use different types of knowledge, as well as cognitive, metacognitive, social and emotional strategies in their daily practices (Xiang et al, 2022).…”
Section: Teachers' Adaptive and Routine Expertise With Playfulnessmentioning
confidence: 99%
“…As the social interactions that occur in daily life at ECE centres are complex, uncertain and ambiguous, teachers' adaptive expertise is characterized by non-linearity, interconnectedness and self-organization (Xiang et al, 2022). Adaptiveness can also be seen as an individual's ability to adjust one's reactions in response to environmental changes (Bohle Carbonell et al, 2014) and to use adequate strategies, including playfulness, to solve problems and relieve tensions (Siklander and Impiö, 2019).…”
Section: Teachers' Adaptive and Routine Expertise With Playfulnessmentioning
confidence: 99%